An investigation of the experiences and perceptions of teachers with regards to staff development in a Namibian secondary school - Nasima, Gideon Emmanuel (Rhodes University, Faculty of Education, Department of Education, 2005)
Staff development (SD) is regarded as an important process, both for the professional growth of teachers and the organizational development of schools. The literature on SD uses the concepts of 'SD', 'professional development' and 'in-service training of teachers' interchangeably. The purpose of this study is to investigate the teachers' experiences and perceptions of SD practices in a Namibian secondary school. This qualitative case study was carried out at the school where I am teaching. Two methods were used to collect the data, namely a blend of semi-structured and unstructured interviews with three teachers and one focus group interview with five teachers. The analysis of the data collected was carried using the method suggested by Taylor and Bogdan (1998) which includes discovery, coding and discounting. These concepts are discussed in Chapter Three. The main finding of this research regards SD at the school as mainly in line with the traditional view. The study also made three other unusual findings that differ from the traditional view of SD held at the school. First, the principal's role as a human resource manager of SD; second the pastoral role of a principal in SD and third the role of teachers' unions in SD. All these findings are important for SD practices in schools and for further research because little is known in the current literature on SD. Finally, this study proposes further research to develop an organizational development (OD) cycle of problem solving to help create an internal policy on SD, which is currently nonexistent at the school.
Keywords: Education -- Namibia; Teachers -- In-service training -- Namibia; School management and organization -- Namibia; School principals -- Namibia